Positive narratives against the destructive behavior of novice voters on social media - Rr. Amanda Pasca Rini; Andik Matulessy; Elza Kusumawati; Daffa Dwi Sri Diyanti (Insight: Jurnal Ilmiah Psikologi, 2024)
Direct elections do not always run well. The aggressiveness of political partisans, who are sometimes hostile – swearing and verbally blaspheming one another on social media – during the campaign triggers a wider public conflict. Teenagers play an active role as novice voters in elections, yet verbal aggression of social conflicts on social media is prone to occur. This study is a multi-year research. In the first year, it mapped down the verbal aggression tendencies of young voters in Indonesia using literature and explanatory studies. It examined the theory and identified factors inducing polite behaviors. It was conducted in several areas around East Java for 6 months. The respondents in this study comprised 500 novice voters from designated provinces, with 100 samples from each. This quantitative research instrument involved verbal aggression, positive thinking, and positive communication as instruments analyzed and measured according to compatible measuring instruments. The study results indicated that teenagers who make the most of logic and common sense in thinking are not susceptible, especially to things that don't make sense. Logic teenagers prefer to ignore bad thoughts. Consequently, they hold a high sense of empathy once communicating, are calm, and tough to be emotionally provoked. Keyword: Polite behavior design; positive thinking; positive behavior; verbal aggressiveness; novice voter.